2012
DOI: 10.5398/medpet.2012.35.1.28
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Repeat Breeding in Dairy Cows under Tropical Condition

Abstract: ABSTRAKPenelitian ini bertujuan untuk mempelajari tingkat kejadian kawin berulang pada ternak sapi perah di daerah tropis. Penelitian ini merupakan studi awal yang dilaksanakan di Kabupaten Sinjai, Indonesia. Sebanyak 82 ekor ternak sapi perah pada lima kelompok tani/ternak digunakan dalam penelitian ini. Sebanyak 75,6% dari 82 ternak sapi perah mengalami kebuntingan setelah beberapa kali dilakukan inseminasi buatan (IB). Tingkat kejadian kawin berulang pada daerah ini sangat tinggi (62%). IB pertama setelah m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…In the present study, no attempt was made to investigate the incidence of repeat breeding syndrome in dairy cows and the contributing factors. However, in our previous study (Yusuf et al, 2012), reported that the incidence of repeat breeding in this area was very high. Therefore, an intensive study is needed to depict the factors which contributing to the incidence of repeat breeding syndrome of dairy cows in this area.…”
Section: Reproductive Failure In Dairy Cowsmentioning
confidence: 68%
See 1 more Smart Citation
“…In the present study, no attempt was made to investigate the incidence of repeat breeding syndrome in dairy cows and the contributing factors. However, in our previous study (Yusuf et al, 2012), reported that the incidence of repeat breeding in this area was very high. Therefore, an intensive study is needed to depict the factors which contributing to the incidence of repeat breeding syndrome of dairy cows in this area.…”
Section: Reproductive Failure In Dairy Cowsmentioning
confidence: 68%
“…The previous study (Yusuf et al, 2010a) indicated that herd, parity, season of calving, resumption of postpartum ovarian cycles, and days in milk at first AI might be contribute in repeat breeding syndrome. The incidence of repeat breeding in this area probably caused by heat stress due to the hot humid weather in tropical condition, resulting in reduce fertility (Yusuf et al, 2012). When dairy cattle are subjected to heat stress, the reproductive efficiency will decline.…”
Section: Reproductive Failure In Dairy Cowsmentioning
confidence: 99%
“…The reproductive efficiency of dairy cows in the tropical area is relatively low with more repeat breeder cases (27) and the average of first artificial insemination after parturition is longer (28) than dairy cows in sub-tropical regions. In addition, BUN concentrations above 18 mg/dL may decrease uterine pH and decrease fertility in dairy cows (12), by affecting the motility and viability of sperm in female reproductive tract so as to decrease pregnancy rate.…”
Section: Bun Concentrations and Reproductive Efficiencymentioning
confidence: 99%
“…It is typically defined that a cow isn't conceived after three or more artificial insemination by an inseminator. Incidence of repeat breeding in dairy cows has been reported by several studies ranging from 11.8% to 62% resulting economic loss in dairy cattle production (Lafi et al, 1992;Katagiri and Takahashi, 2004;Yosuf et al, 2012). Dairy farmers have been suffering a lot due to this evolving trouble.…”
Section: Introductionmentioning
confidence: 99%